Mathematical inequalities : a perspective - Cerone, Pietro (CRC Press, 2010)
"This book provides an overview of the expanding field of mathematical inequalities and their applications. Instead of focusing on narrow treatments of various mathematical inequalities, the authors present a number of classical and recent results across the field, covering integral inequalities, discrete inequalities, and inequalities in abstract spaces. They also make new connections and investigate intimate relationships between inequalities. Written in an accessible manner, the text offers simple proofs for young researchers yet incorporates sufficient detail to appeal to experts and graduate students in real and functional analysis"--